Remnant cholesterol in patients with established cardiovascular disease predicts cardiovascular events both among patients with type 2 diabetes and among non-diabetic subjects. (14th October 2021) - Mader, A; Sprenger, L; Vonbank, A; Larcher, B; Maechler, M; Mutschlechner, B; Benda, M; Leiherer, A; Muendlein, A; Drexel, H; Saely, C H
Abstract:  : Remnant cholesterol, which is calculated as total cholesterol minus LDL cholesterol minus HDL cholesterol has attracted interest as a marker of cardiovascular event risk. The purpose of this study was to investiage whether remnant cholesterol has the power to predict cardiovascular events in patients with established cardiovascular disease. We enrolled 1822 consecutive patients with established cardiovascular disease, including 1472 with angiographically proven stable CAD, 350 with sonographically proven peripheral artery disease. Prospectively, cardiovascular events were recorded over a mean follow-up period of 6.2±3.2 years. At baseline, remnant cholesterol was significantly higher in patients with T2DM (n=608) than in non-diabetic subjects (27±25 vs. 21±21 mg/dl; p<0.001). During follow-up, 584 of our patients suffered cardiovascular events; the event rate was significantly higher in patients with T2DM than in non-diabetic subjects (45.4 vs. 32.2%; p<0.001). Remnant cholesterol in Cox regression models adjusting for age, sex, hypertension, smoking, body mass index and LDL cholesterol independently predicted cardiovascular events in the total study population (standardized adjusted HR 1.15 [1.07–1.23]; p<0.001), and in patients with T2DM as well as in non-diabetic subjects (standardized adjusted HRs 1.17 [1.03–1.34]; p=0.013 and 1.12 [1.01–1.23]; p=0.028, respectively). From our data we conclude that remnant cholesterol in patients with established cardiovascular disease predicts cardiovascular events both among patients with T2DM and among non-diabetic subjects. FUNDunding Acknowledgement: Type of funding sources: None.